PORTABLE SMART MINI PATIENT MONITOR FOR IMPROVED HEALTHCARE OUTCOMES: PATIENT-BASED CARE DEVICE (Pakistan Journal of Science, 2022)
This study aims to present the prototype for Portable Smart Mini Patient Monitor for improved healthcare outcomes and patient-based care that records and displays the vital physiological signs including heartbeats, body temperature, ECG, and SPO2. The device has designed with multiple sensors connected with Arduino UNO and interfaced with an LCD display that provide real-time acquisition of the patient’s data. The recent era of medical advancement and digitization has embarked on the need for efficient and innovative medical devices that provide better admittance to competent and dynamic patient care like the smart mini patient monitor to facilitate substantial diagnosis and treatment of patients’ medical diseases by accurately identifying the pattern and effect of the ailment along with the improved patient experience and healthcare outcomes. The research aims to provide better healthcare opportunities to the patients on daily bases and improve the overall healthcare delivery system and make it work simultaneously with the increased population yearning for medical attention. The smart mini patient monitor was used for the detection of vital signs for five human subjects. The acquired results were then calibrated with a thermometer and BIOPAC device. The main idea of the study dwells upon the incorporation of multiple sensors into one portable device that yields multiple physiological signals at one time with utmost precision and can be easily tracked, stored, and used for medical diagnosis.
Keywords: Patient monitoring; portable sensors; ECG; heartbeats; body temperature and SPO2